Searching for Radioactive Sources by Numerical Fitting Method - Min Zhang, Zhenghua Xu, Xuewen Lu, Shuliang Zou, Yong Liu (Design Engineering, 2020)
In order to locate out-of-control orphan nuclear sources in a short period, we randomly search for out of control orphan source in barrier-free areas by mimicking ideas similar to human search radiation sources. An intelligent random search model with human thinking is established. Based on the complex situations that may occur in real-world search, the single search strategy was optimized, and a random search model with human thinking was established. It is theoretically proved that the time complexity of the algorithm of the search model and the complexity of the average storage space used in the search were linear. For the random search of multi-point radioactive sources, a random search model of two-point radioactive sources was established, and the search success probability of different random search strategies was discussed. We demonstrate the location of the radiation source through a random search algorithm in the simulation environment. The simulation results showed that the optimization algorithm has good efficiency and fault tolerance.